Dietary Fiber as a Good Functional Food Source (Thoyyib) for Digestion - Mujianto, Mujianto; Harahap, Burhanuddin; Robbany, Muhammad Dusturuddin; Sebayang, Nico Syahputra (Universitas Muhammadiyah Palembang, 2023)
People's diets have shifted from containing lots of carbohydrates, fiber and little fat to a healthy lifestyle which includes foods low in carbohydrates, low in fiber and high in protein. Changes in people's eating patterns accompany changes in disease patterns, from infectious diseases to degenerative and metabolic diseases. Several health problems, including heart disease, malignant tumors in the large intestine, and other complications are caused by diet. Therefore, solutions are needed to be provided to the community so that healthy living practices can be restored. Functional foods are natural food additives that have many benefits. Fiber-rich food products are functional foods because they are known to be very good (toyyib) for consumption by sufferers of degenerative diseases. Dietary fiber (DF) has long been researched and found to have many health benefits. Advances in research related to nutrition help food processing businesses. Scientists and sustainable food technologists are working to use dietary fiber in various food products. Vegetables, fruit and seaweed are foods with good sources of fiber. Even though it does not contain many nutrients, dietary fiber provides many health benefits, including controlling body weight (obesity), colon cancer, preventing gastrointestinal disorders, controlling diabetes, and reducing blood cholesterol levels and cardiovascular disease. Although dietary fiber is beneficial for health, it can also be dangerous, so the fiber tolerance limit is 30 grams/day.